Exploring voice barriers and subsequent practices among frontline healthcare workers in Pakistan: a comprehensive mixed-methods analysis - Noreen Kanwal; Ahmad Shahrul Nizam Isha; Al-baraa Abdulrahman Al-Mekhlafi; Rao Irfan Ali Haider (BMC Health Services Research)
Abstract Background Voice barriers among frontline healthcare workers hinder safety related to work and patients. Understanding these barriers and practices is crucial to improve voice behavior in healthcare settings. Therefore, this study aims to identify the voice barriers and practices among healthcare workers in Pakistan. Research method The study has adopted a mixed-method research design. Data was collected from 15 frontline healthcare workers through semi-structured interviews to achieve study objectives. Descriptives and content analysis were conducted to explore voice barriers and alternative practices to solve their concerns. After that, a quantitative study was conducted to determine the statistical significance of the identified voice barriers and the magnitude of their effect. For this purpose, data was collected from 480 frontline healthcare workers in the primary, secondary, and territory healthcare units. A questionnaire survey was used for data collection. Then, multistage hierarchical regression analysis was employed for data analysis. Results Study findings highlight the determinants of two key factors: withholding patient safety concerns and withholding worker safety concerns. First, the study identifies several factors that increase the likelihood of healthcare workers withholding concerns about patient safety. These factors include professional designation, work experience, blackmailing, overconfidence, longer work tenure, feelings of insult, early career stage, fear of patient reactions, bad past experiences, job insecurity, and uncooperative management. Fear of increased workload also plays a significant role. Second, when it comes to work-related safety concerns, factors such as gender, shyness, lack of confidence, fear of duty changes, management issues, interpersonal conflicts, and resource shortages contribute to the withholding of concerns. To navigate these challenges, healthcare workers often resort to strategies such as seeking political connections, personal settlements, transfers, union protests, quitting, using social media, engaging in private practice, or referring patients to other hospitals. Conclusion Findings demonstrates that healthcare workers in Pakistan often withhold safety concerns due to hierarchical pressures, personal insecurities, and fear of repercussions. Their reliance on external mechanisms, such as political influence or social media, underscores the need for significant reforms to improve safety culture and management support. Addressing these issues is crucial for ensuring both patient and worker safety.